2014
DOI: 10.1002/anie.201407452
|View full text |Cite
|
Sign up to set email alerts
|

Reactions in Nitroimidazole Triggered by Low‐Energy (02 eV) Electrons: Methylation at N1‐H Completely Blocks Reactivity

Abstract: Low-energy electrons (LEEs) at energies of less than 2 eV effectively decompose 4-nitroimidazole (4NI) by dissociative electron attachment (DEA). The reactions include simple bond cleavages but also complex reactions involving multiple bond cleavages and formation of new molecules. Both simple and complex reactions are associated with pronounced sharp features in the anionic yields, which are interpreted as vibrational Feshbach resonances acting as effective doorways for DEA. The remarkably rich chemistry of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(93 citation statements)
references
References 18 publications
(22 reference statements)
7
80
0
4
Order By: Relevance
“…These predictions on the dissociation dynamics are in line with the present results for methyl formate, where the formation of O − seems to be completely blocked by the presence of the methyl group. A similar effect in electron-induced chemistry was previously shown for single hydrogen loss in DEA to nucleobases (Ptasińska et al 2005a) as well as in few fragmentation channels of nitroimidazoles upon DEA (Tanzer et al 2014). However, in the latter study this effect was restricted to electron energies below 2 eV.…”
supporting
confidence: 77%
“…These predictions on the dissociation dynamics are in line with the present results for methyl formate, where the formation of O − seems to be completely blocked by the presence of the methyl group. A similar effect in electron-induced chemistry was previously shown for single hydrogen loss in DEA to nucleobases (Ptasińska et al 2005a) as well as in few fragmentation channels of nitroimidazoles upon DEA (Tanzer et al 2014). However, in the latter study this effect was restricted to electron energies below 2 eV.…”
supporting
confidence: 77%
“…It has been suggested that in cells which are deficient of oxygen, the formation of radical anions may play a significant role in action of the radiosensitizer. 12 In our previous communication, 8 the quenching effect of methylation was demonstrated in the case of two DEA reactions. Here we present the complete set of reactions operative in 4NI and its methylated forms Me4NI and Me5NI ( Figure 1).…”
Section: ■ Introductionmentioning
confidence: 82%
“…In a recent communication 8 we demonstrated that electron attachment to 4NI in the 0−8 eV energy range leads to DEA reactions with ion yields characterized by a series of sharp resonances in the very low-energy range (below 2 eV) followed by a broad and unstructured resonance in the energy range between 2 eV and about 5 eV, with a peak maximum near 3.0− 3.5 eV; its exact position is dependent on the fragment ion under observation. Very surprisingly, in the corresponding methylated compound (4MeNI), DEA was completely blocked at energies below 2 eV but still operative within the unstructured and broad resonance at higher energy.…”
Section: ■ Introductionmentioning
confidence: 97%
“…There is also a great potential for other nitro-containing compounds such as nitroimidazolic compounds to be used in radiotherapy, since LEEs effectively induce their dissociation [72,73]. Similarly, their decomposition via DEA involves a range of unimolecular fragmentation channels from simgle-bond cleavages to complex reactions, possibly leading to a complete degradation of the target molecule.…”
Section: Radiosensitizersmentioning
confidence: 99%